iMoFE@tree (Instructional Materials for Office Furniture and Equipment @ Linktree) - Mohd Zulkifli Abdullah; Naliza Solat; Nik Mohd Faris Nik Min; Noor Dalila Musa; Azmi Salim; Nurul Zahidah Md. Juperi; Muhammad Ammar Haidar Ishak (Malaysia Journal of Invention and Innovation, 2022)
In general, instructional materials can motivate students to learn more effectively. With that in mind, the goal of this project is to improve the current learning about office furniture and equipment. With only 4 hours to cover the syllabus, lecturers frequently struggle to cover it. The use of PowerPoint slides is regarded as time-consuming. Students' understanding of this subject is also hampered by the fact that they cannot actually observe office furniture and equipment in class. As a result, iMoFE@tree is recommended to help lecturers and students master the topic. The idea of putting all educational content (infographics, case studies, augmented reality, and data studio) on one page not only demonstrates the project's uniqueness, but it also supports lecturers' engagement and improves students' experience. iMoFE@tree can also help office staff and executives in both public and private organizations who are in charge of managing their office furniture and equipment.